2007
DOI: 10.1002/tea.20183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active‐learning experiences on achievement, attitudes, and behaviors in high school biology

Abstract: Active-learning labs for two topics in high school biology were developed through the collaboration of high school teachers and university faculty and staff and were administered to 408 high school students in six classrooms. The content of instruction and testing was guided by State of Texas science objectives. Detailed teacher records describing daily classroom activities were used to operationalize two types of instruction: active learning, which used the labs; and traditional, which used the teaching resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 17 publications
5
83
1
5
Order By: Relevance
“…Previous studies have indicated that inquiry-based instruction increases students' argumentation skills (Baron, 1991;Driver et al, 2000;Taraban et al, 2007;Tsai, 2001). This study further found that using scientific discourse in presentation provides opportunities to develop students' scientific communication skills.…”
Section: Ilis Approach Intervention Influenced Students' Inquiry Procsupporting
confidence: 71%
“…Previous studies have indicated that inquiry-based instruction increases students' argumentation skills (Baron, 1991;Driver et al, 2000;Taraban et al, 2007;Tsai, 2001). This study further found that using scientific discourse in presentation provides opportunities to develop students' scientific communication skills.…”
Section: Ilis Approach Intervention Influenced Students' Inquiry Procsupporting
confidence: 71%
“…O International Congress of School Improvement and School Efficacy é um exemplo de um organismo internacional de promoção da eficácia educativa, pela via da promoção de estratégias nesse sentido. Na organização escolar, existem evidências de que a promoção de determinadas dimensões tem um impacto significativo positivo nas trajetórias acadêmicas dos alunos (Epstein & Sheldon, 2002;Lee & Burkam, 2003), principalmente quanto a: (a) plasticidade do sistema escolar: capacidade da escola e do contexto educativo de se adaptar às características e necessidades dos alunos (Bryk, Easton, Kerbeow, Rollow, & Sebring, 1994;Reynolds, A. Harris, Clarke, Harris, & James, 2006;Taylor & Adelman, 1999); (b) monitorização constante (Gullatt & Lemoine, 1997;Taylor & Adelman, 1999;Wagstaff, Combs, & Jarvis, 2000); (c) existência de atividades extracurriculares (DeKalb, 1999;Feldman & Matjasko, 2005;Gilman, Meyers, & Perez, 2004); (d) tutoria: desenvolvida por professores ou colegas mais velhos que apoiam os alunos com maiores dificuldades (Gonzales, Richards, & Seeley, 2002;Tierney, Grossman, & Resch, 1995); (e) promoção de atividades de aprendizagem ativa: os alunos realizam suas tarefas de modo autônomo e com os seus pares (Bell & Kozlowski, 2008;Taraban, Box, Myers, Pollard, & Bowen, 2007;Yoder & Hochevar, 2005); (f) aprendizagem individualizada: os professores adaptam suas práticas de ensino a cada aluno (Adelman & Taylor, 1993;W. Stainback & Stainback, 1992;Switzer, 2004); (g) utilização de tecnologias educativas, em casa e na escola (Hartley, 2007;Imel, 1999;Wesley, 2004); e (h) educação para a carreira (Stone, 2004;Stone & Aliaga, 2002).…”
unclassified
“…Constructivism-based instructional materials are commonly classified under the name of 'inquiry-based' and include hands-on activities as a way to inspire and engage learners while concretizing science concepts (Minner, Levy & Century 2009). Hands-on learning activities are consistent with learner-centred strategies based on a constructivist learning-teaching approach (Taraban, Box, Myers, Pollard & Bowen 2007). Inquiry-based learning refers to the pedagogical approach that uses the general processes of scientific inquiry as its teaching and learning methodology (Ketpichainarong, Panijpan & Ruenwongsa 2010).…”
Section: Introductionmentioning
confidence: 99%